2012
DOI: 10.1039/c1mb05156c
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic folding of two intrinsically disordered proteins: searching for conformational selection

Abstract: Intrinsically disordered proteins (IDPs) lack stable structures under physiological conditions but often fold into stable structures upon specific binding. These coupled binding and folding processes underlie the organization of cellular regulatory networks, and a mechanistic understanding is thus of fundamental importance. Here, we investigated the synergistic folding of two IDPs, namely, the NCBD domain of transcription coactivator CBP and the p160 steroid receptor coactivator ACTR, using a topology-based mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
58
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 96 publications
(183 reference statements)
11
58
0
Order By: Relevance
“…Such binding mechanism is consistent with the observed structural plasticity of IDP complexes, where disordered regions search the most stable conformation with specific interactions after the initial encounter event. The presence of intermediate states is also in agreement with recent molecular dynamics simulation studies (17,23) on NCBD/ACTR, where it was suggested that productive on-pathway intermediates may arise through two different pathways. One intermediate was formed by docking of the C-terminal helices and stabilized by the highly conserved and buried salt bridge between Asp-1068 in ACTR and Arg-2104 in NCBD, whereas formation of the second intermediate was found to be initiated by interactions between the N-terminal helices.…”
Section: Discussionsupporting
confidence: 77%
“…Such binding mechanism is consistent with the observed structural plasticity of IDP complexes, where disordered regions search the most stable conformation with specific interactions after the initial encounter event. The presence of intermediate states is also in agreement with recent molecular dynamics simulation studies (17,23) on NCBD/ACTR, where it was suggested that productive on-pathway intermediates may arise through two different pathways. One intermediate was formed by docking of the C-terminal helices and stabilized by the highly conserved and buried salt bridge between Asp-1068 in ACTR and Arg-2104 in NCBD, whereas formation of the second intermediate was found to be initiated by interactions between the N-terminal helices.…”
Section: Discussionsupporting
confidence: 77%
“…75 An earlier simulation study using a single-Gō model, with carefully calibrated secondary structure, similarly predicted an initial formation of inter-protein contacts prior to folding of the NCBD, when binding to ACTR, consistent with our results. 53 The results we obtain with our double-Gō model are completely consistent with the conclusions of our earlier all-atom study of the isolated NCBD. 38 In that work, we found that although the unbound state was still significantly disordered, there was evidence that some features of the binding interface were already present.…”
Section: B Binding Transition Pathssupporting
confidence: 81%
“…46 Gō models have been successful 47 in describing a range of phenomena, from protein folding mechanisms 48 to protein association, 49 domain swapping, 50 protein misfolding, 51 and association of IDPs with their binding partners. 18,19,52,53 However, these models each describe only one folded (and one unfolded) free energy minimum (excepting nativelike intermediates), and would therefore not be appropriate for describing the association of an IDP with two different binding partners where it binds them in very different structures. To address this shortcoming, we have constructed a double-Gō variant which combines Gō potentials derived from different structures into a hybrid system whose partition function at a defined mixing temperature T mix is equal to the sum of the partition functions of the separate Gō potentials at T mix .…”
Section: Model and Methodsmentioning
confidence: 99%
“…Therefore, we introduced additional energetic parameters to match the experimental observations, including structural fluctuations, binding affinity, residual structure, and ionic strength. Overall, our model is substantially different from previous physics-based models (24)(25)(26)(27)(28) and structure-based models (10,11,13,(29)(30)(31)(32)(33)(34)(35) used in the studies of IDPs.…”
mentioning
confidence: 61%
“…Among these 96 replicas in REMD simulations, we focused on investigating the thermodynamic properties at 298 K, which is comparable to the experimental conditions. There are multiple methods to define the formation of a helix in a peptide segment (13,26,28,34). Here, we used three different definitions (SI Appendix) to guarantee the robustness of the analysis.…”
Section: Resultsmentioning
confidence: 99%